A moderated-mediation analysis of pathways in the association between Veterans’ health and their spouse’s relationship satisfaction: The importance of social support - Frank, Christine; Coulthard, Julie; Lee, Jennifer E. C.; Skomorovsky, Alla (Frontiers in Psychology, 2022)
Introduction: Military personnel and Veterans are at increased risk of mental and physical health conditions, which can impact their families. Spouses often perform a vital role in caring for service members and Veterans facing illness or injury, which can lead to caregiver burden. In turn, this may contribute to relationship issues. Research suggests that ensuring that spouses are well supported can alleviate some of these negative effects. The current study examined whether social support received by spouses of newly released Veterans buffers the association of Veterans’ health on caregiver burden, subsequently impacting spouses’ relationship satisfaction. Methods: Data were collected as part of the Canadian Armed Forces Transition and Well-being Survey. The sample included N = 595 spouses of Regular Force Veterans who released in 2016 with at least two years of service. We examined Veterans’ mental and physical health and spouses’ caregiver burden, social support, and relationship satisfaction. A moderated mediation model was tested using structural equation modelling. Results: There was a significant indirect association between Veterans’ health (both physical and mental) and spouses’ relationship satisfaction through caregiver burden. Furthermore, social support moderated the association, as evidenced by a weaker association between Veterans’ health and caregiver burden at low levels (-1SD) of social support compared to high levels (+1SD). Implications: Findings suggest additional efforts should be made to ensure sufficient support is provided to spouses, especially when they are caring for a service member or Veteran facing illness or injury, to strengthen their families’ well-being.